Analysis of harmonics using wavelet technique - Thangaraj. K; Subramaniam. N. P.; Narmada R; Oma Mageswari. M (Institute of Advanced Engineering and Science, 2019)
This paper develops an approach based on wavelet technique for the estimation of harmonic presents in power system signals. The proposed technique divides the power system signals into different frequency sub-bands corresponding to the odd harmonic components of the signal. The algorithm helps to determine both the time and frequency information from the harmonic frequency bands. The comparative study will be done with the input and the results attained from the wavelet transform (WT) for different conditions and Simulation results are given.